The influence of quality of work life and knowlesdge management on organizational citizenship behavior with job satisfaction as a mediating variable.(Study on DPRD Secretariat West Pasaman Regency) - Aulia, Rizki; Yulihasri, Yulihasri; Lukito, Hendra (Institute of Computer Science (IOCS), 2024)
This study aims to analyze the factors influencing organizational citizenship behavior (OCB) at work, including quality of work life and knowledge management with job satisfaction as a mediating variable. The research population is employees of the Secretariat of the Pasaman Barat Regency DPRD with a sample of 66 employees. Using descriptive statistical analysis and factor description with SmartPLS 4.0, the results show that quality of work life and knowledge management have a positive and significant relationship with OCB. Quality of work life and knowledge management also have a positive and significant impact on job satisfaction, which in turn influences OCB positively and significantly. Additionally, job satisfaction significantly mediates the relationship between quality of work life and OCB, as well as knowledge management and OCB.